Dampak Pelatihan Ibu/Pengasuh terhadap Akurasi Pengukuran Lingkar Lengan Atas (LILA) pada Bayi dan Balita untuk Klasifikasi Status Gizi - Haning, Yeny Sunaria; Datta, Frans Umbu; Jutomo, Lewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine whether there are differences in the skills of mothers/caregivers in measuring LILA of their babies and toddlers before and after being given short training. This research method uses interview techniques and direct observation with a pre-experimental analysis method designed by One Group Pre test-Post test. The data obtained were analyzed using the Wilcoxson test and the Fisher's Exact Test statistical test. The results of research at the UPTD Puskesmas Oesapa, Kupang City showed that the skills of mothers/caregivers in measuring LILA before and after being given training obtained a P_value of 0.000. The difference in the LILA measurement method between the simple method and the standard golden method obtained P-value = 0.025 and the relationship between the color of the LILA ribbon and the nutritional status of toddlers with the BB/U and BB/TB or BB/PB index. The conclusion is that there is a significant difference in the skills of mothers/caregivers in measuring LILA before and after being given training, there is a significant difference in the results of measuring LILA between using the simple method and the standard golden method and there is a significant relationship between the color of the LILA ribbon and the nutritional status of toddlers with the BB/U and BB/TB or BB/PB indexes. Keywords: Mother/caregiver Pita LILA, Nutritional Status